2022
DOI: 10.3390/biom13010001
|View full text |Cite
|
Sign up to set email alerts
|

Upcycling Fish By-Products into Bioactive Fish Oil: The Suitability of Microwave-Assisted Extraction

Abstract: The seafood industry is often left out of the food waste discussion, but this sector is no exception, as it generates large amounts of various by-products. This study aimed to explore the potential of the microwave-assisted extraction (MAE) technique to obtain high-quality oil from fish by-products. The independent variables, which were time (1–30 min), microwave power (50–1000 W), and solid/liquid ratio (70–120 g/L) were combined in a 20-run experimental design coupled with the response surface methodology (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…Cellular antioxidant activity (CAA): Pomegranate leaves’ extracts were re-dissolved in water at 8 mg/mL and submitted to successive dilutions with 2′,7′-dichlorohydrofluorescein (DCFH) prepared with ethanol and diluted with HBSS (50 μM), acquired from Hyclone company (Logan, Utah, USA), to obtain the final concentrations to be tested (32.5–2000 μg/mL). This cell-based process was carried out as stated by Pinela et al [ 73 ] using a murine macrophage cell line (RAW 246.7) acquired from Leibniz-Institute DSMZ. The cells were maintained with DMEM supplemented with 10% heat-inactivated FBS, glutamine (2 mM), penicillin (100 U/mL), and streptomycin (100 μg/mL) and left to proliferate in an incubator at 37 °C, 5% CO 2 , and humified atmosphere (Heal Force CO 2 Incubator, Shanghai Lishen Scientific Equipment Co, Ltd., Shangai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Cellular antioxidant activity (CAA): Pomegranate leaves’ extracts were re-dissolved in water at 8 mg/mL and submitted to successive dilutions with 2′,7′-dichlorohydrofluorescein (DCFH) prepared with ethanol and diluted with HBSS (50 μM), acquired from Hyclone company (Logan, Utah, USA), to obtain the final concentrations to be tested (32.5–2000 μg/mL). This cell-based process was carried out as stated by Pinela et al [ 73 ] using a murine macrophage cell line (RAW 246.7) acquired from Leibniz-Institute DSMZ. The cells were maintained with DMEM supplemented with 10% heat-inactivated FBS, glutamine (2 mM), penicillin (100 U/mL), and streptomycin (100 μg/mL) and left to proliferate in an incubator at 37 °C, 5% CO 2 , and humified atmosphere (Heal Force CO 2 Incubator, Shanghai Lishen Scientific Equipment Co, Ltd., Shangai, China).…”
Section: Methodsmentioning
confidence: 99%
“…There is a wide range of available by-products stemming from different food industrial sectors that can be found in both the vegetable and animal worlds [111,112].…”
Section: Recent Patents and Industrial Valorization Of Vegetable By-p...mentioning
confidence: 99%
“…UAE combined with enzymes or SFE improved oil extraction from fish meal. , MAE could extract high-quality oil from fish byproducts without loss of functionality of PUFA. Under optimal MAE conditions, 60 and 100% of oil could be recovered in about 19 min with less solvent consumption . As high as 20% oil was isolated from sardine waste with SC–CO 2 .…”
Section: Green Extractions Of Ingredients From Seafood Side Streamsmentioning
confidence: 99%
“…Under optimal MAE conditions, 60 and 100% of oil could be recovered in about 19 min with less solvent consumption. 96 As high as 20% oil was isolated from sardine waste with SC− CO 2 . 81 The high price of fish oils makes the various technologies viable for the extraction process.…”
Section: Proteinsmentioning
confidence: 99%